Is British output growth related to its uncertainty? Evidence using eight centuries of data. (8th March 2021) - Bredin, Don; Fountas, Stilianos; Savva, Christos
Abstract: We examine the empirical relationship between output variability and output growth for Britain using data for eight centuries covering the 1270 to 2014 period. Drawing on the economic history literature, we split the full sample period into four subperiods and use GARCH models to measure output growth uncertainty and estimate its effect on average growth. Within each sub‐sample, we allow output growth to depend on the state of the system, for example 2‐regime switching model would switch between high‐growth and low‐growth regimes. We find that the effect of uncertainty on growth differs depending on the existing growth regime. Low‐growth regimes are associated with a negative effect of uncertainty on growth, and medium or high‐growth regimes are associated with a positive effect. These findings are consistent across the four states of economic development. Our results indicate why the empirical literature to date has found mixed results when examining the effect of uncertainty on growth.